VOLATILITY OF INTEGRATED INDICATORS SERIES OF OIL AND GAS ENTERPRISES’ FINANCIAL CONDITION AT RISK - Khvostina, I.M. (The actual problems of regional economy development, 2020)
The article is aimed at studying the trend of time series of integrated indicators of the financial condition of oil and gas companies, using the methods of financial analysis and taxonomic procedures. This article reveals the main patterns of development of the oil and gas industry, which are impossible without studying the relationship between economic processes and business risks. Problems of functioning and development of oil and gas production enterprises of Ukraine are considered. Indicators of volumes from sales, import and export of 25 leaders of oil and gas enterprises of Ukraine are investigated, as a result of which their import orientation is proved. An analysis of the dynamics of liquidity, solvency, profitability and business activity of oil and gas companies in Ukraine, resulting in a decrease in indicators, which demonstrates a certain signaling ability to reduce the financial stability of oil and gas companies and increase the overall level of financial risks. Taxonomic procedures were used to build an integrated indicator of the financial condition of oil and gas companies of Ukraine for the period 2015-2019. This approach to risk management will provide a comprehensive description of the object of study and more fully depict the prospects for further development, create adequate systems of analytical support for management decisions, their improvement and adaptation to the needs of oil and gas companies.